Perilaku Organisasi dalam Penanggulangan Bencana Daerah di Kabupaten Buton Selatan - La Ode Dwiyan Pramono Darmin; La Parasit; Jasir B. Jasir B.; Ilham Ilham (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2024)
This research describes organizational behavior in disaster management in South Buton Regency. The study employs a qualitative method with data collection techniques using triangulation (interview, observation, and documentation). Data substance reduction is then presented for analysis. The analysis in this research utilizes Robins & Judge’s organizational behavior model with three levels of analysis. The findings of research include, among others, at the individual level, the South Buton Regency’s Disaster Management Agency (BPBD) exhibits diverse attitude, perception sensitive to disaster mitigation, and motivation requiring effective management. To achieve optimal performance in disaster management, there is a need for management strategies that understand the uniqueness of each individual, create a supportive organizational culture, and motivate employees with clear guidance. At the group level, effective leadership, structured communication, and proper conflict resolution are essential for achieving goals and optimal performance in BPBD South Buton Regency. At the organizational level, organizational structure, organizational culture, and human resource management in BPBD South Buton Regency have been formed and operated effectively. This structure aims to establish formal task distribution, create unity, and enable effective coordination and collaboration in achieving organizational goals.